PARTICIPATION IN TOURIST FAIRS AS A FACTOR OF DESTINATION AREAS’ ACTIVATION - Niemczyk, Agata; Seweryn, Renata (Acta Scientiarum Polonorum. Oeconomia, 2010)
Huge competition in the tourist market is forcing the entities acting on it, including the territorial units, to search for effective forms to distinguish themselves, in order to attract more and more visitors, or at least to keep current ones. The popularizing of the destination areas as an attractive spaces for tourists should be made in well-designed promotional activity, paying particular attention not only to the media, but above all to participation in the fair events. The aim of the article is to show the role of promotion through the tourist fairs in the activation of the destination areas. The results of research of the exhibitors at the Cracow Tourism Salon 2010 constitute the empirical base of this paper.